Evolution of idealism - Copeland, Minnie Laura (My University, 1898)
Introduction: The dominating power of man is the will – A dual monarchy – an aristocracy: Realism and Idealism – Contrasting terms yet one often embodies the other – neither is complete without the other – no mind is totally devoid of either – which dominates determines the character of its abode in this life, whether man or brute, ruler or serf , heaven or hell.
Citation: Copeland, Minnie Laura. Evolution of idealism. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Man; Will; Dual Monarchy; Aristocracy; Realism; Idealism; Theses; Manuscripts (documents)